Premature menopause and autoimmune primary ovarian insufficiency in two international multi-center cohorts. Issue 5 (25th May 2022) - Vogt, Elinor Chelsom; Real, Francisco Gómez; Husebye, Eystein Sverre; Björnsdottir, Sigridur; Benediktsdottir, Bryndis; Bertelsen, Randi Jacobsen; Demoly, Pascal; Franklin, Karl Anders; de Aja Gallastegui, Leire Sainz; González, Francisco Javier Callejas; Heinrich, Joachim; Holm, Mathias; et al.
Abstract : Objective: To investigate markers of premature menopause (<40 years) and specifically the prevalence of autoimmune primary ovarian insufficiency (POI) in European women. Design: Postmenopausal women were categorized according to age at menopause and self-reported reason for menopause in a cross-sectional analysis of 6870 women. Methods: Variables associated with the timing of menopause and hormone measurements of 17β-estradiol and follicle-stimulating hormone were explored using multivariable logistic regression analysis. Specific immunoprecipitating assays of steroidogenic autoantibodies against 21-hydroxylase (21-OH), side-chain cleavage enzyme (anti-SCC) and 17alpha-hydroxylase (17 OH), as well as NACHT leucine-rich-repeat protein 5 were used to identify women with likely autoimmune POI. Results: Premature menopause was identified in 2.8% of women, and these women had higher frequencies of nulliparity (37.4% vs 19.7%), obesity (28.7% vs 21.4%), osteoporosis (17.1% vs 11.6%), hormone replacement therapy (59.1% vs 36.9%) and never smokers (60.1% vs 50.9%) ( P < 0.05), compared to women with menopause ≥40 years. Iatrogenic causes were found in 91 (47%) and non-ovarian causes in 27 (14%) women, while 77 (39%) women were classified as POI of unknown cause, resulting in a 1.1% prevalence of idiopathic POI. After adjustments nulliparity was the only variable significantly associated with POI (odds ratio 2.46; 95% CI 1.63–3.42). Based on the presence of autoantibodies against 21 OH and SCC, 4.5% of POI cases were of likely autoimmune origin. Conclusion: Idiopathic POI affects 1.1% of all women and almost half of the women with premature menopause. Autoimmunity explains 4.5% of these cases judged by positive steroidogenic autoantibodies.